STRATEGI GURU DALAM MENSTIMULASI KEMAMPUAN ANAK BERKOMUNIKASI SAAT PEMBELAJARAN DITAMAN KANAK-KANAK PEMBANGUNAN - Sri Cahaya Sihombing; Serli Marlina (Universitas Islam Lamongan, 2022)
Based on researchers from researchers regarding children's communication during learning at the Taman Kanak-kanak Pembangunan Laboratorium Universitas Negeri Padang, they found that children were seen to be passive in learning. Children seem to communicate less during learning, tend to be more silent than respond to the learning that the teacher gives. However, after being observed again, over time the children who looked passive became more active in communicating in each learning process. The purpose of this study was to describe how the teacher's strategy to stimulate children's ability to communicate during learning in Taman Kanak-kanak Pembangunan Laboratorium Universitas egeri Padang. This study used descriptive qualitative method. Informants in this study were principals and teachers at the Taman Kanak-kanak Pembangunan Laboratorium Universitas Negeri Padang. Data collection techniques consisting of observation, interviews and documentation. Data analysis techniques were carried out by collecting data, reducing data, presenting data, and drawing conclusions. While the data validity technique uses triangulation techniques. The results are generally known that the teacher's strategy in improving communication skills during learning is done by using simple language when communicating with children during learning, then using challenging conversations to stimulate children to communicate, using intentional communication, and using learning methods and learning media as learning support. So it can be said that teachers in stimulating children's communication during learning can be done using simple language, challenging conversations, intensive communication, methods and also learning media